2020
DOI: 10.3905/jor.2020.1.079
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Racial/Ethnic Retirement Wealth Inequality

Abstract: is to produce first-class research and forge a strong link between the academic community and decision-makers in the public and private sectors around an issue of critical importance to the nation's future. To achieve this mission, the Center sponsors a wide variety of research projects, transmits new findings to a broad audience, trains new scholars, and broadens access to valuable data sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…The authors suggested that this can be explained by the SSA's progressive formula increasing social security wealth of low-income individuals in the post-retirement years, reducing the gap between non-Hispanic whites and Hispanics. Our analysis is supported by Hou and Sanzenbacher (2020), who found that social security wealth provides, on average, a 95% replacement rate (ratio between social security wealth and pre-retirement income) for Hispanic households. Hou and Sanzenbacher (2020) found other types of wealth, such as employer-provided pensions and financial and housing wealth, were more unequal for non-Hispanic whites and Hispanics after retirement, and that this led to financial insecurity in old age for Hispanics.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The authors suggested that this can be explained by the SSA's progressive formula increasing social security wealth of low-income individuals in the post-retirement years, reducing the gap between non-Hispanic whites and Hispanics. Our analysis is supported by Hou and Sanzenbacher (2020), who found that social security wealth provides, on average, a 95% replacement rate (ratio between social security wealth and pre-retirement income) for Hispanic households. Hou and Sanzenbacher (2020) found other types of wealth, such as employer-provided pensions and financial and housing wealth, were more unequal for non-Hispanic whites and Hispanics after retirement, and that this led to financial insecurity in old age for Hispanics.…”
Section: Discussionsupporting
confidence: 74%
“…Our analysis is supported by Hou and Sanzenbacher (2020), who found that social security wealth provides, on average, a 95% replacement rate (ratio between social security wealth and pre-retirement income) for Hispanic households. Hou and Sanzenbacher (2020) found other types of wealth, such as employer-provided pensions and financial and housing wealth, were more unequal for non-Hispanic whites and Hispanics after retirement, and that this led to financial insecurity in old age for Hispanics. Dettling et al (2017) found that non-Hispanic white homeowners held more home equity than Hispanics and had more diversified asset portfolios, including business ownership, private retirement accounts, and financial savings (stocks, bonds, and mutual funds).…”
Section: Discussionsupporting
confidence: 74%
“…Social Security is an important asset for most lower‐income families, including many Black people, because it replaces a larger share of preretirement earnings for beneficiaries with limited lifetime earnings than for those with more earnings. Expanding household wealth measures to include Social Security reduces the racial gap in wealth, although differences remain substantial (Hou & Sanzenbacher, 2020; Wolff, 2018).…”
Section: The Racial Gap In Economic Well‐being At Older Agesmentioning
confidence: 99%
“…Black people are less likely than White people to be married (Johnson, Haaga, & Simms, 2011), which allows households to economize on living expenses; to receive inheritances (Hamilton & Darity, 2010), which can help finance home purchases and fund retirement; and to have access to banks, which facilitates saving (Federal Deposit Insurance Corporation, 2018). Consequently, Black families generally hold much less wealth than White families (Dettling et al, 2017;Hou & Sanzenbacher, 2020;Wolf, 2018). This article documents the financial challenges facing older Black adults and discusses various policy options to improve their financial well-being.…”
mentioning
confidence: 99%
“…Commercial pension insurance products offer individuals the opportunity to accumulate funds through regular contributions, which are then invested in various financial instruments to generate returns. [2] Upon retirement, these accumulated funds are used to provide a steady income stream, supplementing other sources of retirement income. The appeal of commercial pension insurance products lies in their potential to address the limitations of traditional pension systems.…”
Section: Introduction 11 Background and Contextmentioning
confidence: 99%